Intentions to stay and employment prospects of refugees from Ukraine - Tetyana Panchenko; Panu Poutvaara (CESifo GmbH, 2022)
We conducted two waves of quantitative online surveys and qualitative interviews of Ukrainian refugees in Germany. We asked whether they plan to stay in Germany and whether they are already employed or plan to search for employment, as well as the factors that determine these. We report the results of the second wave of surveys in this policy brief. The second wave of the survey clarified the socio-demographic characteristics of refugees from Ukraine, the circumstances of their arrival and adaptation in Germany, and demonstrates the dynamics of changes in their plans and intentions.
Keywords: 330